2022
DOI: 10.1136/annrheumdis-2022-222460
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait and cross-population genome-wide association studies across autoimmune and allergic diseases identify shared and distinct genetic component

Abstract: ObjectivesAutoimmune and allergic diseases are outcomes of the dysregulation of the immune system. Our study aimed to elucidate differences or shared components in genetic backgrounds between autoimmune and allergic diseases.MethodsWe estimated genetic correlation and performed multi-trait and cross-population genome-wide association study (GWAS) meta-analysis of six immune-related diseases: rheumatoid arthritis, Graves’ disease, type 1 diabetes for autoimmune diseases and asthma, atopic dermatitis and pollino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 57 publications
0
25
0
1
Order By: Relevance
“…We used the four-factor model identified in EFA and included the disorders with loadings greater than |0.3| in each factor. The CFA analysis in GenomicSEM showed a good fit of the model to the data (χ 2 (12) =16.1; AIC =64.1; CFI = 0.98; SRMR = 0.07). The first factor included VITE, VITL and MG. MG, RA and SLE were included in the second factor, while the third factor consisted of T1D, PSC and MG (with a negative loading).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…We used the four-factor model identified in EFA and included the disorders with loadings greater than |0.3| in each factor. The CFA analysis in GenomicSEM showed a good fit of the model to the data (χ 2 (12) =16.1; AIC =64.1; CFI = 0.98; SRMR = 0.07). The first factor included VITE, VITL and MG. MG, RA and SLE were included in the second factor, while the third factor consisted of T1D, PSC and MG (with a negative loading).…”
Section: Resultsmentioning
confidence: 94%
“…The genetic correlation across multiple ADs has not been fully explored (11,12). So far, crossdisorder GWAS meta-analyses have only focused on a few ADs, usually three to seven at a time (12)(13)(14)(15), while others have only focused on pairwise meta-analyses (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rheumatoid arthritis (RA) and type 2 diabetes (T2D) GWAS from UKBB have moderate and significant correlations with asthma, which are partially recapitulated in the BBJ results that showed a moderate but not significant correlation between the BBJ GWAS of RA and of asthma, and a small but significant correlation between the BBJ GWAS of T2D and the GBMI leave-BBJ-out meta-analysis of asthma. Several studies in the literature have reported a relationship between risk for RA and asthma [73][74][75][76][77][78] , as well as T2D and asthma [79][80][81] , but more genetic studies in different populations and biobanks are needed to investigate the potential shared genetic architecture of these diseases. Importantly, causal relationships between asthma and genetically correlated phenotypes are not yet well-understood, and other methods such as Mendelian randomization could be applied to identify potential causal associations 82 .…”
Section: Genetic Overlap Between Asthma and Other Diseasesmentioning
confidence: 99%